2017
DOI: 10.1111/cas.13249
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of methotrexate‐associated lymphoproliferative disorders: Comparison of diffuse large B‐cell lymphoma and classical Hodgkin lymphoma types

Abstract: Patients with rheumatoid arthritis often develop methotrexate‐associated lymphoproliferative disorders (MTX‐LPD) during MTX treatment. MTX‐LPD occasionally regresses spontaneously after simply discontinuing MTX treatment. In patients without spontaneous regression, additional chemotherapy is required to avoid disease progression. However, the differences between spontaneous and non‐spontaneous regression have yet to be elucidated. To clarify the factors important for spontaneous regression, we analyzed the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 15 publications
(49 reference statements)
7
91
1
Order By: Relevance
“…By contrast, the majority of patients with classical HL-type MTX-LPD (76%) required additional chemotherapy (17). Corticosteroids are used in combination with cyclophosphamide or chemotherapy for the treatment of malignant lymphoma, whereas a previous study reported the use of rituximab (18). In keeping with our results, another study also demonstrated that corticosteroid pulse therapy was effective (12).…”
Section: Discussionsupporting
confidence: 84%
“…By contrast, the majority of patients with classical HL-type MTX-LPD (76%) required additional chemotherapy (17). Corticosteroids are used in combination with cyclophosphamide or chemotherapy for the treatment of malignant lymphoma, whereas a previous study reported the use of rituximab (18). In keeping with our results, another study also demonstrated that corticosteroid pulse therapy was effective (12).…”
Section: Discussionsupporting
confidence: 84%
“…This high positive rate may be partly explained by the fact that 75% of mixed cellularity subtype CHLs have been reported to be EBER-positive (1); all the MTX-CHL cases in this study were mixed cellularity subtype. On the other hand, none of our MTX-CHL cases were positive for CD20, which is consistent with a previous study that reported only one CD20-positive case among 17 MTX-CHL cases (4). In contrast, 38% of our sporadic CHL cases were positive for CD20, which is comparable to previous reports (18-40%) (1,11,12).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, although extranodal disease is reported to be generally rare in sporadic CHL (1,13), we identified it in 28% of our sporadic CHL cases. Fifty percent of patients with MTX-CHL had extranodal disease in our study, which is in agreement with previous studies that reported high rates of advanced-stage CHL and extranodal disease in 40-70% of patients with MTX-CHL (4,7,14). Therefore, high rates of advancedstage CHL and extranodal disease are also typical clinical characteristics of MTX-CHL.…”
Section: Discussionsupporting
confidence: 92%
“…In a phase II study of nivolumab for HL, a correlation was observed between the level of PD-L1 expressed on tumor cells and the efficacy of nivolumab (22). Since the majority of cases of MTX-CHL are positive for EBV (12)(13)(14)(15)23), nivolumab may be more beneficial as a treatment option for advanced-stage MTX-HL due to the stronger expression of PD-L1, than for earlystage disease. Clinical trials on nivolumab for EBV-positive lymphomas are ongoing (NCT03258567, NCT02973113), and this issue may be clarified based on the findings obtained therein.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an autoimmune disease, and patients treated with methotrexate (MTX) occasionally develop lymphoproliferative disorders (MTX-LPDs) several years after the initiation of its administration (11). The majority of MTX-LPDs are diffuse large B-cell lymphomas, among which CHL accounts for 10-30% (MTX-CHL) (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%